Isotemporal substitution of sedentary time with different physical activity intensities and sleep in obesity parameters across eight latin American countries - Eduardo Rossato de Victo; Diego Sales; Diego G. D. Christofaro; Mauro Fisberg; Irina Kovalskys; Pablo del Val Martín; Gerson Ferrari (Scientific Reports)
Abstract This study aimed to examine the associations between substituting sedentary time (ST) with physical activity and sleep with obesity parameters in adults from eight Latin American countries. The sample consisted of 2173 adults aged 18–65 years. Physical activity, ST and sleep were objectively measured using accelerometers. The parameters of obesity were defined using body mass index (BMI) and waist circumference (WC). Regression analyses were conducted for isotemporal analysis of the association between substituting 30 min/day of ST with light physical activity (LPA), moderate to vigorous physical activity (MVPA) and sleep in relation to BMI and WC. Substituting light physical activity with higher intensity was also analyzed. Substituting 30 min/day of ST with MVPA was significantly associated with lower odds of a higher BMI (OR: 0.993, 95%CI 0.990–0.998) and WC (OR: 0.998, 95%CI 0.998–0.999). Conversely, substituting ST with LPA did not show a significant impact on obesity parameters. However, the substitution of 30 min/day of LPA with MVPA was also associated with lower odds of a higher BMI (OR: 0.993, 95%CI 0.989–0.997). The results highlight the importance of replacing ST and increasing the intensity of physical activity as an effective strategy for preventing and managing obesity in Latin America.